2009
DOI: 10.1001/archsurg.2008.528
|View full text |Cite
|
Sign up to set email alerts
|

The Formula for a Successful Laparoscopic Skills Curriculum

Abstract: Although multiple simulators have been validated as effective training tools, curriculum development is lagging, and considerable work is needed to determine the best methods for training. This article identifies the factors that influence the successful incorporation of simulator training into the resident curriculum, reviews the evidence regarding laparoscopic curriculum development in the surgical literature, and provides a formula for effective curriculum design. A successful laparoscopic skills curriculum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(118 citation statements)
references
References 56 publications
3
109
0
6
Order By: Relevance
“…[15][16][17] Branded as the ''Fundamentals of Laparoscopic Surgery'' (FLS) program, this curriculum has been validated by multiple studies across surgical specialities as a laparoscopic surgical skill assessment and training tool. 15,16,[18][19][20][21] We, therefore, sought to compare the impact of 2D versus 3D visualization on laparoscopic performance using components of the validated FLS skill set.…”
Section: Journal Of Laparoendoscopic and Advanced Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Branded as the ''Fundamentals of Laparoscopic Surgery'' (FLS) program, this curriculum has been validated by multiple studies across surgical specialities as a laparoscopic surgical skill assessment and training tool. 15,16,[18][19][20][21] We, therefore, sought to compare the impact of 2D versus 3D visualization on laparoscopic performance using components of the validated FLS skill set.…”
Section: Journal Of Laparoendoscopic and Advanced Surgical Techniquesmentioning
confidence: 99%
“…1,12 We sought to overcome this limitation by basing our assessment of laparoscopic proficiency in the current analysis on components of the standardized FLS curriculum. Developed by SAGES 15 and endorsed by the American College of Surgeons, 18,19 the FLS program has now been validated as a laparoscopic surgical skill assessment and training tool in multiple studies across specialty lines. 16,18,20,21 Fried et al 15 demonstrated that FLS scores increased progressively with increasing laparoscopic experience among general surgeons (n = 215, P < .0001) and that surgery residents followed over time increased their FLS scores (n = 24, P < .0001), thus providing evidence of construct validity.…”
Section: D Versus 3d Vision: Impact On Fls Performancementioning
confidence: 99%
“…Indubitavelmente, no futuro, os simuladores se tornarão uma parte integrante do currículo da maioria dos programas cirúrgicos. Dessa forma, as seguintes considerações podem ser inferidas da literatura: 1) a simulação integrada na educação neurocirúrgica deve ser feita principalmente tendo em mente o ensino dos residentes [28]; 2) no treinamento do residente, é essencial a integração da simulação com um currículo formalizado [26]; 3) a combinação de diferentes modalidades de simulação parece ser efetiva, assim, residentes em níveis diferentes de treinamento devem diversificar os tipos de simulação, com evidentes benefícios educacionais; 4) a distribuição de tempo de prática permite a aquisição mais eficiente da habilidade quando se utiliza a simulação para propósitos educacionais [29]; 5) realizar avaliação periódica do cirurgião relativa à performance após a simulação é importante para se obter o máximo benefício [30].…”
Section: Estado Da Arte Em Simulação Cirúrgicaunclassified
“…The Web-based training video (WBTV) contains a large collection of streaming and downloadable HD quality videos of surgical procedures, combined with how-to step-by-step surgical teaching guidelines to aid the implementation of laparoscopic surgical procedures for various surgical disciplines. 24,25 Further, just recently, the first interactive e-learning program for laparoscopy has been introduced. 25 The elearning program is called ''SimpraxisTM Laparoscopic Cholecystectomy Trainer'', a customizable, interactive, simulation software training platform for cognitive learning of surgical procedures.…”
Section: -10mentioning
confidence: 99%